2020
DOI: 10.1080/15592324.2020.1792187
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma virens colonization of maize roots triggers rapid accumulation of 12-oxophytodienoate and two ᵧ-ketols in leaves as priming agents of induced systemic resistance

Abstract: Trichodermavirens colonization of maize roots triggers rapid accumulation of 12-oxophytodienoate and two ᵧ-ketols in leaves as priming agents of induced systemic resistance,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Despite that we noted the enhanced resistance of maize stems to GSR by exogenously applied MeJA, this effect is likely due to the induction of oxylipins other than JA. MeJAinducible resistance to GSR is likely independent of COI1a, or due to the yet unknown JA-independent defense pathways induced by MeJA, such as 9-LOX signaling pathways as shown recently for a 9-oxylipin alfa-ketol KODA of gamma-ketols [27,28]. Another candidate molecule is probably 12-OPDA that was recently shown to induce resistance to other hemibiotrophic pathogens [27] (Figure 7).…”
Section: Maize Susceptibility To F Graminearum Is Promoted By Ja and Coi1amentioning
confidence: 79%
See 2 more Smart Citations
“…Despite that we noted the enhanced resistance of maize stems to GSR by exogenously applied MeJA, this effect is likely due to the induction of oxylipins other than JA. MeJAinducible resistance to GSR is likely independent of COI1a, or due to the yet unknown JA-independent defense pathways induced by MeJA, such as 9-LOX signaling pathways as shown recently for a 9-oxylipin alfa-ketol KODA of gamma-ketols [27,28]. Another candidate molecule is probably 12-OPDA that was recently shown to induce resistance to other hemibiotrophic pathogens [27] (Figure 7).…”
Section: Maize Susceptibility To F Graminearum Is Promoted By Ja and Coi1amentioning
confidence: 79%
“…[18] and Fusarium verticillioides [20], but resistant to anthracnose leaf blight and stalk rot, caused by a hemibiotrophic pathogen Colletotrichum graminicola [21]. Although underappreciated previously, 12-OPDA has been increasingly drawing attention as having functions distinct from those of JAs [22][23][24][25][26][27]. Particularly, a recent study revealed that 12-OPDA and α-ketol of octadecadienoic acid (KODA), but not JA, serve as the mobile signals in Trichodema-elicited induced systemic resistance (ISR) [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 13-hydroxy-10-oxo-(11E,15Z)-octadecadienoic acid (13,10-KODA) did not come close to statistical difference at this timepoint, but was significantly higher in PLV-treated plants at 4 dpi. Importantly, we have previously shown that exogenous treatments with several of these ketols, including the α-ketol 9,10-KODA (Wang et al, 2020a), and the γ-ketols, 9,12-KOMA and 9,12-KODA (Wang et al, 2020b), strongly increase maize resistance to C. graminicola.…”
Section: Plv-mediated Resistance To C Graminicola Correlates With Increased Synthesis Of Oxylipin Hydroxides and αAnd γ-Ketolsmentioning
confidence: 99%
“…Furthermore, Trichoderma spp. induce the expression of genes related to defense, such as the plant defensin 1.2 gene (PDF1.2) and the pathogenesis-related 1a gene (PR-1a), which are used as markers for ISR-priming and SAR, respectively [19,[22][23][24][25]. In addition, some proteins of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%